HUBUNGAN TINGKAT PENGETAHUAN PERAWAT TENTANG PROSEDUR PELAYANAN PASIEN DENGAN RESPONSE TIME DI RUANG INSTALASI GAWAT DARURAT RSUD dr. SOEDOMO TRENGGALEK) - Renata Eka Febriyanti; Rahayu Niningasih; Edi Yuswantoro (Suluh Adiluhung Publisher (SAPub), 2026)
The Emergency Department (ED) is a hospital unit that requires rapid and accurate management of emergency patients, particularly in meeting response time standards. This study aimed to analyze the relationship between nurses’ knowledge of patient care procedures and response time in the Emergency Department of RSUD dr. Soedomo Trenggalek. This study employed an analytic observational design with a cross-sectional approach. All 14 nurses working in the Emergency Department were included as respondents using a total sampling technique. Nurses’ knowledge was assessed using a questionnaire, while response time was measured through an observation checklist. Data were analyzed using univariate and bivariate analyses. The results showed that 11 out of 14 nurses (78.6%) had a good level of knowledge regarding patient care procedures, and 13 out of 14 nurses (92.9%) demonstrated fast response times in accordance with emergency service standards. Bivariate analysis revealed a statistically significant relationship between nurses’ knowledge of patient care procedures and response time in the Emergency Department (p = 0.032). This study concludes that nurses’ knowledge is significantly associated with the timeliness of emergency response services.